KYAI SOLEH DARAT, TAFSIR FA'ID AL-RAHMAN DAN RA. KARTINI - Masrur, Mohammad (At-Taqaddum, 2012)
One of the intellectual heritages of Islam in Java pre modernism. That deserve gets appreciation is the work of shaykh Muhammad  ibn Salih al-Samarani Umar , who among Kyai (clerics) in Java is know as ?Saleh Kyai Darat?. Tafsir Faid  al- Rahman fi Tarjamah Kalam Malik Dayyan is a monumental work has ever written by him, this Tafseer (interpretation) is not complete 30 Juz, it?s just till the Tafseer (interpretation) of the letter al-nisa, consists of two large volumes of 705 pages thick, Both were printed by the publicher of al-Muhammadiyah, Singapore between the years 1309-1312 H.There are two important notes that need further explored related to the interpretation of the Faid al-Rahman. First, this Tafseer book was specifically written by Kyai Soleh Darat met/fulfill the demands of RA. Kartini, Second, this book had given by Kyai Saleh Darat to RA. Kartini as a gift/gists upon her marriage with RM. Joyodiningrat, who is a Regent of Rembang at the time.